Some High Value Medicinal Plants of Khumbu Region Nepal - Rawal, Deepa Shree; Sijapati, Jaishree; Rana, Neesha; Rana, Prabina; Giri, Anjana; Shrestha, Sangita (Nepal Journal of Science and Technology, 2010)
Visualizing the present biodiversity status of Nepal, an integrated approach comprising of biodiversity documentation, bio-prospecting, sustainable utilization and conservation has become an urgent need. Realizing the importance of medicinal plants altogether 45 plants were collected from Khumbu region with the altitudinal variation of 2582m to 4470m. Among the collected plant species 12 have been characterized as highly valuable. The important biochemical constituents and morphology of these plants have been described in this paper. Key words: Himalayan region; Khumbu; Medicinal plants; Morphological characters DOI: 10.3126/njst.v10i0.2828 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 73-82